SRATEGI GURU DALAM MENGINTEGRASIKAN KEARIFAN LOKAL KE DALAM PEMBELAJARAN SBDP DI SEKOLAH DASAR - Maghfirotul Ulia; Wasis Wijayanto; Shokifatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Teachers must instill local wisdom in primary school SBDP classes in order to develop character, which is the cornerstone for the creation of a wealthy and civilized society. Understanding the theory of learning techniques found in the local knowledge of cultural arts in elementary school institutions is the aim of this study. The information examined in this research is derived from interviews with SD 4 Puyoh Kudus' Cultural Arts instructor, Mr. Anang Setyawan Jodi, S.Pd., Gr. The idea of learning methodologies focused on incorporating local wisdom through SBDP learning in primary schools is the foundation for the intended outcomes.Keywords: Local wisdom, SBDP learning, learning strategies Keywords: Local wisdom, SBDP learning, learning strategies